Nonalcoholic Fatty Liver Disease is Associated With Erectile Dysfunction: A Prospective Pilot Study - ÇELİKEL, ÇİĞDEM; DUMAN, DENİZ (ELSEVIER SCI LTD, 2016)
Introduction: Nonalcoholic fatty liver disease (NAFLD) is considered the hepatic manifestation of metabolic syndrome (MetS). Although the link between MetS and erectile dysfunction (ED) is well known, clinical studies investigating the association between NAFLD and ED are scant. Aim: To evaluate the relationship between NAFLD and ED. Methods: Male patients with biopsy-proven NAFLD were prospectively asked to fill the five-item International Index of Erectile Function (IIEF-5) questionnaire. Their clinical and histologic variables were compared with the IEFF scores. Main Outcome Measures: IIEF scores; proportions of NAFLD patients who demonstrated ED and/or MetS; association between the severity of histological hepatic damage and ED. Results: Forty male patients having an age range of 33 (24-57) and a mean age of 40.13 +/- 10.22 years with biopsy-proven NAFLD had a median IIEF-5 score of 16 (9-25) and MetS was present in 23 (57.5%). ED severity distributions as moderate, mild, and no ED were 11 (27.5%), 16 (40%), and 13 (32.5 %), respectively. Histological NAFLD score was significantly higher in patients having ED compared with patients with no ED (5.63 +/- 1.39 vs 4.15 +/- 1.46; P = .006). MetS diagnosis was significantly more common in patients having ED, compared with those without ED [19 (70.4%) vs 4 (30.8%), respectively, P = .018)]. When patients with and without ED were compared, gamma glutamyl transferase was significantly lower in ED, whereas components of MetS did not correlate with ED. After multivariate analysis, NAFLD score has remained the only significant outcome associated with ED [P = .03; OR (95% CI): 2.38 (1.079-5.238)]. Conclusion: The current clinical study demonstrates a significant association between nonalcoholic steatohepatitis and ED for the first time. Our findings suggest liver damage may play role in the pathogenesis of ED in patients with NAFLD. Future studies are needed to expand the underlying common mechanisms responsible for this novel hypothesis. Copyright (C) 2016, International Society for Sexual Medicine. Published by Elsevier Inc. All rights reserved.
Keywords: Erectile Dysfunction; Nonalcoholic Fatty Liver Disease; Nonalcoholic Steatohepatitis; Fatty Liver; Metabolic Syndrome; INTERNATIONAL INDEX; INSULIN-RESISTANCE; METABOLIC SYNDROME; STEATOHEPATITIS; VALIDATION; VERSION